2002
DOI: 10.4049/jimmunol.168.6.3079
|View full text |Cite
|
Sign up to set email alerts
|

Skin Inflammation During Contact Hypersensitivity Is Mediated by Early Recruitment of CD8+ T Cytotoxic 1 Cells Inducing Keratinocyte Apoptosis

Abstract: Contact hypersensitivity (CHS) is a T cell-mediated, Ag-specific skin inflammation induced by skin exposure to haptens in sensitized individuals. Th1/T cytotoxic 1 cells are effector cells of CHS, whereas Th2/T regulatory CD4+ T cells have down-regulating properties. We have previously shown that CHS to 2,4-dinitrofluorobenzene is mediated by specific CD8+ effector cells, whose cytolytic activity is mandatory for induction of skin inflammation. In this study, using immunohistochemistry and RT-PCR analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
195
1
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(216 citation statements)
references
References 59 publications
12
195
1
8
Order By: Relevance
“…Upon skin painting, the hapten is taken up by skin DC which migrate to proximal lymph nodes and activate specific T cells. Since the hapten can stay in the skin for a few days in its antigenic form, effector CD8 + T cells are recruited and activated in the dermis and induce CHS through a process involving cytotoxicity and IFNγ synthesis [38,39]. We used suboptimal concentrations of DNFB so that the CHS reaction observed at day 5 was only moderate in intensity and magnitude (Fig.…”
Section: Lpc Primes Specific T Cell Responses In Vivomentioning
confidence: 99%
“…Upon skin painting, the hapten is taken up by skin DC which migrate to proximal lymph nodes and activate specific T cells. Since the hapten can stay in the skin for a few days in its antigenic form, effector CD8 + T cells are recruited and activated in the dermis and induce CHS through a process involving cytotoxicity and IFNγ synthesis [38,39]. We used suboptimal concentrations of DNFB so that the CHS reaction observed at day 5 was only moderate in intensity and magnitude (Fig.…”
Section: Lpc Primes Specific T Cell Responses In Vivomentioning
confidence: 99%
“…Previous studies have shown that CD8 1 T cells are able to infiltrate quickly into inflamed sites [18] that may facilitate their early interaction with DCs. In human psoriasis studies, the administration of alefacept, which reduces infiltration of activated memory CD8 1 T cells, reduced DC content, inflammation and tissue expression of iNOS and IFN-g [19].…”
Section: Introductionmentioning
confidence: 99%
“…CD8 1 T cells utilize a variety of factors, including IFN-g, GM-CSF, TNF-a and CD40L to activate DCs for the production of 13,14], the key cytokine for Th1 immunity [15]. Importantly, CD8 1 T cells were shown to interact with DCs in both lymph nodes [16] and peripheral tissue sites [4,17] where they exert their pro-Th1 influence.Previous studies have shown that CD8 1 T cells are able to infiltrate quickly into inflamed sites [18] that may facilitate their early interaction with DCs. In human psoriasis studies, the administration of alefacept, which reduces infiltration of activated memory CD8 1 T cells, reduced DC content, inflammation and tissue expression of iNOS and .…”
mentioning
confidence: 99%
“…For HPRT, CD4, CD8, IFN-␥ the primers have been described elsewhere (19). For IL-4, the sense primer is 5Ј-TCGGCATTTTGAACGAG GTC-3Ј and antisense 5Ј-GAAAAGCCCGAAAGAGTCTC-3Ј.…”
Section: Rna Extraction and Rt-pcr Analysismentioning
confidence: 99%